Jangan Ada Phubbing di Antara Kita: Studi Personifikasi Perempuan dalam Amsal 8-9 bagi Pemanfaatan Gawai - Yusak Setianto; Muryati, Muryati; Melvin Abrillian (Institut Agama Kristen Negeri Manado, 2023)
Gadgets have caused some users to experience phubbing, especially millennials. If this is allowed, their self-quality and social relations will worsen. Therefore, this study aims to explain the personification of women in Proverbs 8-9 and their relationship with gadgets, so that they can use gadgets wisely. This research method is qualitative descriptive based on a literature study. The results show that gadgets and the personification of women have three positive and negative elements in common: attractiveness, desire for relationships, and impact. This means that gadgets are like a knife that can be useful for cutting food if used correctly, and also killing humans if used incorrectly. That is why all users are advised to choose the path of wisdom, not foolishness, so that phubbing can be avoided. The way is to build an intimate relationship with God and fear Him. So, this study concludes that they must utilize gadgets, not be utilized by them. In other words, they need to use gadgets when it is necessary, not to satisfy desires, waste time, or distance themselves from physical socialization.